A differential feedback scheduling decision algorithm based on mimic defense - Ming GAO; Jin LUO; Huiying ZHOU; Hai JIAO; Lili YING (Dianxin kexue)
Facing the security problem of the service path, according to the service function chain deployment mimic defense architecture based on dynamic heterogeneous redundancy (DHR) model in the mimic defense theory, and combined with the actual needs of the service path deployment, a differential feedback scheduling decision algorithm based on mimic defense was proposed. Firstly, according to the heterogeneity of the executive set in the scheduling algorithm and the security defense coefficient, the scheduler suitable for the mimic defense scenario was selected from the executive pool, and then the decider was selected according to the reliability coefficient of the decision algorithm and the majority decision algorithm. The proposed algorithm, common scheduling algorithm and decision algo rithm were simulated and analyzed. Simulation results show that the proposed algorithm can effectively improve the system’s defense capabilities and ensure the security of the service path configuration.